An Examination of the Citizenship Status of Stateless Foreigners Married to Indonesians - Ridha Nikmatus Shahada; Muhammad Azzam Alfarizi; Lisa Arianti Kusuma Dewi (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The existence of Stateless in the territory of Indonesia is quite widely spread in various regions. Some of them are refugees and foreigners who do not have an identity and do not get recognition from the embassies of their home countries. Some of them,stateless live inside rudenim and outside rudenim as stipulated in the laws and regulations. Stateless who live a life outside rudenim not infrequently meets indonesian citizens and they get married. Marriages performed by Indonesian citizens with people who do not have citizenship are questioned because of the unfulfillment of the conditions for the marriage. There are no specific regulations governing this so there is a legal vacuum related to this marriage. Therefore, this research was conducted with normative studies with primarylegal material obtained from laws and regulations such as the 1945 Constitution, Law No. 1 of 1974 on Marriage, Law No. 12 of 2006 on Citizenship, and the Convention Act of 1951. The conclusion of this study is that the marriage conducted is invalid because it is not in accordance with the Marriage Act, the status of stateless person citizenship is not changed to Indonesian citizen, but the citizenship status of the child born can become an Indonesian citizen.